Correction: Gold alloy-based nanozyme sensor arrays for biothiol detection. Issue 11 (30th April 2020) - Lin, Junshu; Wang, Quan; Wang, Xiaoyu; Zhu, Yunyao; Zhou, Xi; Wei, Hui
Abstract : Correction for 'Gold alloy-based nanozyme sensor arrays for biothiol detection' by Junshu Lin et al., Analyst, 2020, ; DOI: 10.1039/d0an00451k .